Broadscale postseismic deformation and lower crustal relaxation in the central Bayankala Block (central Tibetan Plateau) observed using InSAR data. (1st April 2018) - Zhao, Dezheng; Qu, Chunyan; Shan, Xinjian; Zuo, Ronghu; Liu, Yunhua; Gong, Wenyu; Zhang, Guohong
Graphical abstract: Highlights: A postseismic deformation rate map spanning a period of ∼7.2 years is generated. Postseismic motion affects eastward extrusion of the central Bayankala Block. Three models to obtain the best fit viscosity of lower crust are constructed. Lower crust relaxation is the main mechanism of postseismic motion during observation. Abstract: We have generated a more than 500 km long postseismic deformation rate map and cumulative displacement time series in the central Bayankala Block of the Tibetan Plateau using ENVISAT/ASAR data from 2003 to 2010 by the π-RATE stacking algorithm. This rate map spans a period of ∼7.2 years and reveals that postseismic motion of 2001 Kokoxili earthquake exhibits a striking signal, dominating crustal deformation of the central Bayankala Block with a cross-fault magnitude ∼9–11 mm/yr in line of sight (LOS) (∼93.1°E). The southern and northern parts of the postseismic deformation field exhibit different patterns and variable magnitudes, reflecting asymmetry of the displacement distribution. Postseismic motion affects eastward extrusion of the central Bayankala Block, which reaches ∼15 km north of the Ganzi-Yushu fault. To further investigate viscoelastic relaxation of the lower crust in this area after approximately two years, E-M, E-M-M and E-S models are constructed. The result shows that the best fit viscosity for the lower crust is about 1 × 10 19  Pa·s. Comparison between cumulative displacements resolved by these three models shows that viscoelastic relaxation of the lower crust makes the most significant contribution to postseismic stress relaxation after 2001 event.